TINJAUAN HUKUM ISLAM TERHADAP TRADISI PENYALURAN ZAKAT PADI - R Fauzi (JCH (Jurnal Cendekia Hukum), 2017)
Batuhampar village community's habit of making direct alms payments made by the muzaki. They do not want to give their alms to receiver to be distributed, they are more inclined to directly plant alms to the people they want. In addition, the tradition that exists in the village Batuhampar community is that they do not directly pay alms on their rice yields. They will pay alms after only a few days or even more. They also do not pay alms with rice but have been replaced by money, no one is concerned if full charity directly with rice. Furthermore, in calculating the nisab and payment of rice alms, the community does not incur agricultural operational costs. They argue that the calculation of calculation and alms payment is not a valid expense incurred costs and debts earlier. This research is a field research that is research with interview techniques to the parties directly related to the problems that the author discussed. The type of this research is  qualitative research. Based on the research that has been done then the authors can get conclusions from the tradition of zalcat distribution of rice harvest conducted by  Batuhampar village society is legal according to Islamic law. The reason is that the various traditions that have developed in the village Batuhampar community in distributing alms of rice crops are a tradition that is equally absent and not prohibited by Islam. In addition, the tradition of distribution of rice harvest is a tradition that has been perfected both by society and no errors in the implementation.